Anti-CXCL9, anti-CXCL 10, anti-CXCL 11, anti-CXCL 13, anti-CXCR3 and anti-CXCR5 agents for inflammatory disorder - LILLARD JAMES W (2015)
A method for detecting an inflammatory disease in a subject is disclosed. The method comprises the steps of (a) detecting a level of expression of one or more inflammatory disease markers in a biological sample obtained from the subject; and (b) comparing the level of expression of said one or more inflammatory disease markers in the biological sample to a normal level of expression of the one or more inflammatory disease markers, wherein the one or more inflammatory disease markers comprise one or more markers selected from the group consisting of CXCL9, CXCLIO, CXCLl 1, CXCLl 3, CXCR3 and CXCR5. Also disclosed are a method for monitoring the course of treatment for an inflammatory disease in a subject and a kit for detecting an inflammatory disease in a subject.